The multilayered effects and support received by victims of the Bali bombings : a cross cultural study in Indonesia and Australia - Brookes, Gwendoline Patricia (Curtin University, 2010)
Introduction. In the past decade terrorist attacks and suicide bombings have killed, injured and intimidated thousands of people in many countries. In the aftermath of an attack a significant proportion of the population present with symptoms of depression, post traumatic stress disorder, and physical health problems (Boscarino & Adams, 2009, Norris et al., 2002, Bride, 2007 ). The present study examined the impact of the Bali bombings in 2002 when two bombs were deliberately exploded in the Sari night club and Paddy’s bar, in the popular tourist area of Kuta, in Bali, Indonesia.Aim of the study. The overarching aim of the study were to examine the multilayered effects and forms of support received by directly affected victims and their indirectly affected family members in both Indonesia and Australia. The perceptions of members of the Indonesian and Australian emergency response teams, community volunteers and key informants were also examined.Methods. A qualitative case study approach was used in this study, as it was important that participants told their story in their own words and according to their own unique experiences. In total 50 in-depth semi-structured interviews were conducted in Bali and Perth, with first and secondary level victims, professional and volunteer responders, and key informants. An in-depth analysis of available literature was also undertaken with a focus on the multilayered effects of terrorist attacks and the forms of post attack support that is offered to victims and their families. Other qualitative methods such as home visits, observations and documentary data collection facilitated triangulation of the data. In addition a personal reflective diary recorded the observations of the researcher during a two month field trip in Bali in early 2008.The conceptual framework for this study was based around the work of the Psychosocial Working Group (2003). Within this framework three dimensions relating to resources that help people cope in the aftermath of a disaster are explored. They are: human capacity (encompassing the skills and knowledge of the people); social ecology (encompassing familial, religious and cultural resources) and finally culture and values (encompassing cultural values, beliefs and practices). The framework was modified in this study to enhance the examination of the participant responses using the concepts of disrupted and reinforced resources.Results. In both Bali and Perth victims of all levels reported many symptoms of distress in the initial aftermath of the bombing. Most of the effects reported could be termed normal distress reactions to a very abnormal event. The poor economic situation in Bali appeared to compound and exacerbate the effects for many of the Balinese victims. As a result many of the injured and their families were left almost destitute. A number of victims described symptoms such as depression, suicidal ideations and fear during thunderstorms and the many cultural celebrations on the island.In Bali and Perth, first level victims described the importance of practical, economic, emotional and spiritual support from their families and the community. The narratives of mateship, families and communities responding to help are innumerable and are an invaluable and unique insight into this disaster. In addition, the study highlighted that many of the volunteer and professional responders also reported effects such as emotional numbing and derealisation. For most it was a temporary and understandable reaction to the difficult tasks they had to undertake.Recommendations for policy, practice and a modified framework are proposed that may be used by professionals and non-professionals in the aftermath of a terrorist attack, particularly when needing to choose appropriate and culturally relevant interventions, or by organisations who may be involved in strategically planning a response in the event of an attack.Conclusion. Although the focus of this study was a terrorist attack, the recommendations and framework proposed in chapter 9 of this study can be generalised to other forms of natural and man-made disasters. They are intended for use by professionals, nonprofessionals and agencies who are involved in a response in the aftermath of complex emergencies. The recommendations are derived and drawn from the indepth analysis of the participant interviews, and the literature. The Bali disaster showed the strength of human spirit, the resilience of victims at multiple levels and the willingness of people and countries to help each other in times of extreme distress. This framework is intended to promote a psychosocial response to any disaster situation based on the knowledge that communities have pre-existing inherent resources which can be utilised in a terrorist attack.